Air-Independent Powered Submarines in the Asia-Pacific: Proliferation and Repercussions - Bitzinger, Richard A. (2016)
Singapore’s recent acquisition of submarines with air-independent propulsion (AIP) is being matched by similar purchases by other regional navies. While AIP-equipped submarines do not necessary upset regional military balances, they are part of a larger trend in regional naval expansion which could have far-reaching repercussions.